A Proposal to Strengthen Knowledge Management Practice Through Literate Culture - Arwin A. Nugraha; Dedy Sushandoyo (Green Publisher Indonesia, 2025)
Given the potential gap between Company organizational capacity and the anticipated workload required to implement programs, this study was conducted to answer how can literacy culture be integrated to strengthen Knowledge Management practices, and what solutions can be proposed to strengthen Knowledge Management practices through literacy culture. A qualitative research approach was employed, combining semi-structured interviews with key stakeholders and secondary data analysis. The study utilizes Design Thinking to capture employee perspectives and expectations in KM, also extract the insight from former Company Top Leader regarding the use of the narrative success story framework in leadership assessment. The study found the clear understanding of needs and the requirements of alternative solution to be developed. Based on these findings, a complementary KM platform was developed using the Six Sigma DMADV framework, resulting in the creation of proposed digital KM platform for narrative writing and knowledge sharing. The platform incorporates structured writing guidance, competency-based knowledge categorization, and an intuitive user interface to enhance accessibility and engagement. The proposed platform provides a structured yet flexible KM environment that fosters collaboration and continuous learning. This study contributes to KM research by offering a novel approach to KM enhancement through the integration of literate culture in form of narrative success stories and competency-based categorization. It provides actionable recommendations for organizations seeking to improve KM effectiveness in dynamic business environments.